2015
DOI: 10.1007/s13224-015-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of PET–CT Scan in Gynaeconcology

Abstract: The purpose of this study This study was undertaken to evaluate the role of positron emission tomography-CT (PET-CT) in diagnosis and management of gynecological malignancies in primary and recurrent settings and also to investigate its role in inappropriately treated patients, for pretreatment evaluation (staging) to help in proper therapeutic management. Method This is a retrospective study of 56 patients of gynecological malignancy registered in Gujarat Cancer Research Institute from June 2011 to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Pawar et al assessed the success rate of PET/CT in a retrospective study of 56 patients with gynecological malignancy including cervix carcinomas (23 patients). It was shown that PET/CT offers a high diagnostic accuracy, both in the evaluation of suspected tumor recurrence and in persistent disease [ 26 ]. The authors concluded that PET/CT has particular value in primary cervical cancer, which is related to the diagnosis of extra-pelvic abnormalities, the detection of recurrence, and the monitoring of patients after treatment [ 26 ].…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Pawar et al assessed the success rate of PET/CT in a retrospective study of 56 patients with gynecological malignancy including cervix carcinomas (23 patients). It was shown that PET/CT offers a high diagnostic accuracy, both in the evaluation of suspected tumor recurrence and in persistent disease [ 26 ]. The authors concluded that PET/CT has particular value in primary cervical cancer, which is related to the diagnosis of extra-pelvic abnormalities, the detection of recurrence, and the monitoring of patients after treatment [ 26 ].…”
Section: Cervical Cancermentioning
confidence: 99%
“…It was shown that PET/CT offers a high diagnostic accuracy, both in the evaluation of suspected tumor recurrence and in persistent disease [ 26 ]. The authors concluded that PET/CT has particular value in primary cervical cancer, which is related to the diagnosis of extra-pelvic abnormalities, the detection of recurrence, and the monitoring of patients after treatment [ 26 ]. In another retrospective analysis of the accuracy of [ 18 F]FDG PET/CT, the rate of success in the initial stages of cervical tumors was estimated to be 100% [ 27 ].…”
Section: Cervical Cancermentioning
confidence: 99%